Barriers to Men’s Help Seeking for Intimate Partner Violence - Taylor, Julie C.; Bates, Elizabeth A.; Colosi, Attilio; Creer, Andrew J. (Journal of interpersonal violence, 2022)
Evidence suggests that male victims of intimate partner violence (IPV) are less likely to seek help for their victimization than female victims. Studies exploring barriers to help seeking are relatively scarce in the United Kingdom (UK) and those that have been undertaken across Europe, United States, Canada, and Australia have tended to rely on small samples of help-seeking men who have self-identified as victims of IPV. With a view to include more male victim voices in the literature, an anonymous qualitative questionnaire was distributed via social media. In total, 147 men (85% from the UK) who self-identified as being subject to abuse from their female partners, completed the questionnaire. The data was subjected to a deductive thematic analysis and one superordinate and two overarching themes were identified. The superordinate theme was stigmatized gender and the two overarching themes (subthemes in parentheses) were barriers prohibiting help seeking (status and credibility, health and well-being) and responses to initial help seeking (discreditation, exclusion/isolation, and helpfulness). The findings are discussed in the context of Overstreet and Quinn’s (2013) interpersonal violence and stigma model and findings from previous research. The conclusions and recommendations promote education and training and advocate a radical change to policy.